Pengarauh Terpaan Konten Video #OOTD di TikTok Terhadap Perilaku Konsumtif Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Riau - Pramudia Nugroho; Rumyeni (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2024)
The social media that is currently dominating and widely used is TikTok. The features in the TikTok app are very diverse, one of which is hashtags. One video content often seen on TikTok is #OOTD or outfit of the day. This study aimed to see the effect of exposure to #OOTD video content on the consumptive behavior of students of the Faculty of Economics and Business of Riau University. The research method used is quantitative, with an explanatory approach and a questionnaire as the main instrument in data collection. In determining the sample using the unknown population formula and the results obtained were 100 respondents. Purposive sampling was used as a sampling technique. The S-R theory is used, whereas the stimulus-response theory assumes that spoken words (oral-written), non-verbal cues, pictures, and specific actions stimulate other people to respond a certain way. Based on the results of this study, the independent variable (X) #OOTD Video Content on TikTok has an influence of 48.5% on the dependent variable (Y) Consumptive Behavior of students of the Faculty of Economics and Business, Riau University. This, H0 is rejected, and Ha is accepted.